Influence of social support on cognitive function in the elderly - Yeh Shu-Chuan; Liu Yea-Ying (BMC, 2003)
Abstract Background Social support is important in daily activities of the elderly. This study tests the hypothesis that there is an association between social support and cognitive function among the elderly in a community setting. Methods Face-to-face interviews were conducted in a cross-sectional stratified random sample of 4,993 elderly (≥65 years) city residents. Using multiple regression analysis, we investigated the influence of social support on cognitive function. Results 12% were over 80 years old. 53.28% were men. 67.14% were married. Higher Short Portable Mental Status Questionnaire (SPMSQ) scores (higher score means better cognitive function) were associated with strong social support, as measured by marital status and perceived positive support from friends. Lower cognitive function was associated with older and with female respondents. Only instrumental activities of daily living (IADL) were statistically and negatively related to SPMSQ. Lower functional status was associated with lower cognitive function. Elders with grade school educations had lower SPMSQ scores than did elders with high school educations. Conclusions In Taiwan, higher cognitive function in community-living elderly was associated with increased social support. Life-style management should provide social activities for the elderly to promote a better quality of life.